Passing the litmus test : are we preparing youth to manage basic health care needs? A preliminary investigation - Trout, Alexandra L.; Lambert, Matthew C.; Epstein, Michael H; Avery, Marybell (Social Welfare: Interdisciplinary Approach, 2014)
Although there has been growing awareness regarding the importance of health literacy on the social, emotional, and health related outcomes of adults, little is known about the preparedness of high school adolescents to access, navigate, and use health related information and services as they begin to enter into independence. This study evaluates the health literacy skills of 199 youth enrolled in high school health classes in a Midwestern region in the United States. Results revealed that nearly one out of three youth demonstrated some level of risk on applied measures of health literacy, and approximately half were unaware of how to access health insurance, regularly thought about what they eat and how it influences their health, knew how to make medical and dental appointments, and were aware of their family medical history. Implications, study limitations, and recommendations for practice and future research are discussed.
Keywords: health care needs; health literacy skills; health literacy; youth health-related status